2005
DOI: 10.1007/s00402-005-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Mycobacterium infections of the upper extremity

Abstract: Surgical debridement and appropriate mycobacterial culture or PCR method are critical to enable diagnosis and appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Rifampicin has been also used effectively in isolated cases, either alone [30,62] or in combination with other antibiotics [37,38,43,44,51] , antimycobacterials [30,35] , antibiotics plus antimycobacterials [19,42,45,48] , and with antimicrobials plus surgery [30,31,49,50,[63][64][65] . Rifabutin has been administered successfully with clarithromycin [51] .…”
Section: Antimycobacterial Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rifampicin has been also used effectively in isolated cases, either alone [30,62] or in combination with other antibiotics [37,38,43,44,51] , antimycobacterials [30,35] , antibiotics plus antimycobacterials [19,42,45,48] , and with antimicrobials plus surgery [30,31,49,50,[63][64][65] . Rifabutin has been administered successfully with clarithromycin [51] .…”
Section: Antimycobacterial Agentsmentioning
confidence: 99%
“…It has rarely been used as monotherapy, but in combination with rifampicin or with other antimycobacterials [3,15] , with antibiotics [17,46,47,53,54] or a combination of antibiotics and antimycobacterials [29,42,45] and with surgery plus antimicrobacterials [26,49,50,63] .…”
Section: Antimycobacterial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,8,21 However, there is a lack of consensus regarding both the drugs of choice and the duration of treatment. Zenone et al and others 1,3,8 suggested empirically beginning antimicrobial therapy in the immediate postoperative period if there is high clinical suspicion of mycobacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…More than ten species have been described to cause tenosynovitis [24], the most common being M. marinum and M. kansasii. Most infections were related to exposure to contaminated water sources, trauma, or iatrogenic procedures such as steroid injections [17,24]. Infections with M. Chelonae have also been reported to occur without an inciting event [14].…”
Section: Discussionmentioning
confidence: 99%